New Insights and Interdisciplinary Approaches to Study Linguistics - الجاف, علي اسماعيل (lark, 2019)
Linguistics is the study of Languages.  This goes all the way from identifying the sounds of a language to making policies about language use.  Because language is such a fundamental part of who we are, understanding how it works and all the information that it contains can help us understand a whole of other things too.  Languages are the basis of all of our interactions and thoughts.  Worldwide, we speak over 6000 distinct languages, with many more dialects and regional varieties.  The paper concentrates on understanding how languages work, who uses them, why they can be useful to us and what we can do with them in a big task, but there is a discipline and an approach with new ideas about linguistics as a science.